Các quy định pháp luật về quản lý viện trợ đối với quốc gia và vay vốn nước ngoài của doanh nghiệp (Chính Trị Quốc Gia, 1998)
Giới thiệu các quy định pháp luật về quản lý viện trợ đối với quốc gia và vay vốn nước ngoài của doanh nghiệp